2017
DOI: 10.1038/s41598-017-01043-5
|View full text |Cite|
|
Sign up to set email alerts
|

AMPK signaling in the nucleus accumbens core mediates cue-induced reinstatement of cocaine seeking

Abstract: Relapse to drug seeking can be caused by exposure to drug-associated cues, provoking drug craving even after prolonged abstinence. Recent studies demonstrated that AMP-activated protein kinase (AMPK) regulates neuronal morphology and membrane excitability in neurons. Here, we investigated the role of AMPK activity in the nucleus accumbens (NAc) in relapse to cocaine seeking. We found that exposure to drug-related cues reinstated cocaine-seeking behavior and increased AMPK and p70s6k phosphorylation in the NAc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 73 publications
3
29
0
Order By: Relevance
“…p70S6k then phosphorylates ribosomal protein s6 (s6), a component of the 40S subunit of the ribosome (Chung et al, 1992). Changes in p70s6k have been reported following intraperitoneal cocaine injections (Sutton and Caron, 2015; but see Bailey et al, 2012), CPP (Yu et al, 2013;Shi et al, 2014), and cue-induced reinstatement Gao et al, 2017). Here, we found a modest trend toward increased p-p70s6k (Thr389) levels in the cocaine group compared with saline controls (Fig.…”
Section: Incubation Of Craving and Mtor-related Signalingsupporting
confidence: 59%
See 2 more Smart Citations
“…p70S6k then phosphorylates ribosomal protein s6 (s6), a component of the 40S subunit of the ribosome (Chung et al, 1992). Changes in p70s6k have been reported following intraperitoneal cocaine injections (Sutton and Caron, 2015; but see Bailey et al, 2012), CPP (Yu et al, 2013;Shi et al, 2014), and cue-induced reinstatement Gao et al, 2017). Here, we found a modest trend toward increased p-p70s6k (Thr389) levels in the cocaine group compared with saline controls (Fig.…”
Section: Incubation Of Craving and Mtor-related Signalingsupporting
confidence: 59%
“…Nonetheless, our results point to an important role for specific translation pathways in the expression of incubation. mTOR pathway mTOR signaling is implicated in animal models of cocaine addiction (Neasta et al, 2014), including sensitization (Wu et al, 2011;Bailey et al, 2012), CPP (Bailey et al, 2012Yu et al, 2013;, and measures of motivation or relapse following cocaine self-administration James et al, 2014;Gao et al, 2017). In addition, mTOR regulates GluA1 expression (Slipczuk et al, 2009;Neasta et al, 2010;James et al, 2014James et al, , 2016 through local translation (Schratt et al, 2004;Beckley et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that rapamycin‐mediated changes in conditioned reward and sensitized behavior do not likely involve a reversal of cocaine's effects upon mTOR signaling within corticolimbic regions, suggesting that rapamycin interacts with some other cocaine‐induced neuroadaptation(s), independent of the downstream targets of mTOR to exert its apparent ‘anti‐addictive' and ‘anti‐sensitizing' effects. A recent study showed that AMPK activity in the NAc core was critical for the cue‐induced reinstatement of cocaine seeking, which might be mediated by mTORC1 and ERK1/2 signaling . Consistent with these studies, our results revealed that AMPK was activated following cocaine treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, changes in mTOR signaling have been suggested to play an etiological role in the pathology of schizophrenia 60 . Given that mTOR represents one of the main effector pathways via which AMPK connects bioenergetic fluctuations to changes in synaptic transmission 43,44,61 and neurodevelopment 47,48 , we propose that targeting the AMPK-mTOR signaling axis might represent a novel therapeutic approach in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%